2012
DOI: 10.1590/s0102-695x2012005000040
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents from three medicinal plants: Piper renitens, Siparuna guianensis and Alternanthera brasiliana

Abstract: Chemical study of three medicinal plants: from leaves of Piper renitens (Miq.) Yunck, Piperaceae, and Siparuna guianensis Aubl., Siparunaceae, and from flowers of Alternanthera brasiliana (L.) Kuntze, Amaranthaceae, resulted in isolation of nine compounds: three steroids, β-sitosterol, stigmasterol from P. renitens and sitosterol-3-O-β-D-glucopyranoside from A. brasiliana, the diterpene kaurane ent-kauran-16α,17-diol from P. renitens, two derivatives kaempferolmethylether, kumatakenine (kaempferol-3,7-dimethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In a study of the essential oil of its leaves, twenty-five compounds were identified (Facundo et al, 2012;Wakabayashi et al, 2010). More recently, identified three flavones (Wakabayashi et al, 2010).…”
Section: Phytochemical Studiesmentioning
confidence: 99%
“…In a study of the essential oil of its leaves, twenty-five compounds were identified (Facundo et al, 2012;Wakabayashi et al, 2010). More recently, identified three flavones (Wakabayashi et al, 2010).…”
Section: Phytochemical Studiesmentioning
confidence: 99%
“…Moreover, its activity as an antiproliferative, anti-inflammatory, antiedematous and antioxidant, has been reported. It also shows activity against the herpes simplex virus and, recently, anticonvulsant effect (Lagrota et al,1994;Macedo et al, 1999Macedo et al, , 2011Facundo et al, 2012;Andreazza et al, 2013;Schallenberger et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
“…Alternanthera brasiliana is used in folk medicine to treat infections and is popularly known as "terramycin", "penicillin" or "benzetacil" (Facundo et al, 2012;Caetano et al, 2002). In relation to its phytochemistry, several constituents have already been isolated or identified.…”
Section: Introductionmentioning
confidence: 99%